REWARD AND PUNISHMENT ANALYSIS ON O-RANGER MOBILE PT. POS INDONESIA SURABAYA 60000 - Muchammad Hasyim; Nur Cahyadi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this research is to find out the rewards and punishments that occur in o-ranger employees at PT. Pos Indonesia Surabaya 60000. Rewards can be in the form of salary, incentives, welfare, benefits, social, development, career, and psychological rewards. While punishment can be in the form of light punishment, moderate punishment, and severe punishment. Rewards that have been carried out by PT. Pos Indonesia Surabaya 60000 for o-ranger employees, namely giving bonuses in the form of credit money once every 1 month and given to employees whose income reaches the target. While punishment is carried out if the employee commits a criminal offense or does not make a rate deposit for 3 days. The punishment given is in the form of a verbal warning and deactivating the o-ranger employee's account. This study uses a qualitative descriptive approach, and uses data collection techniques in the form of in-depth interviews. The results of this study indicate that the provision of reward and punishment greatly affects the work productivity of employees so that it can increase the company's income.